2015
DOI: 10.1007/s00268-015-3324-x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Cancers After Radiation Therapy for Primary Prostate or Rectal Cancer

Abstract: Literature about the risk of secondary cancer after radiation therapy (RT) of prostate and rectal cancer reveals contradictory results. We conducted a meta-analysis to examine whether the RT induces secondary rectal or prostate cancer in patients, respectively, with prostate or rectal cancer. All studies published in Medline or Pubmed up to March 3, 2015, containing RT of primary rectal or prostate cancer, and providing risk estimates of secondary prostate or rectal cancer were considered as eligible. Relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 71 publications
1
18
0
Order By: Relevance
“…In current meta-analysis, the incidence of some cancers such as esophageal, stomach, liver, gallbladder, lung, thyroid and central nervous system compared to the normal population, was not only higher, but was also lower. According to some reports, the incidence of rectal cancer in patients with prostate malignancy is not significantly different from the general population [11].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In current meta-analysis, the incidence of some cancers such as esophageal, stomach, liver, gallbladder, lung, thyroid and central nervous system compared to the normal population, was not only higher, but was also lower. According to some reports, the incidence of rectal cancer in patients with prostate malignancy is not significantly different from the general population [11].…”
Section: Discussionmentioning
confidence: 94%
“…In a study, Lee et al assessed the risk of radiation therapy-induced secondary malignancies in patients with prostate and rectal cancer [11]. Also, in a meta-analysis study, Jin et al examined the incidence of secondary malignancies in patients with prostate cancer following radiotherapy [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies evaluated also the impact of RT technique on the incidence of second tumors. In particular, three meta-analyses uniformly recorded a higher incidence of second rectal tumors after EBRT but not after brachytherapy [4,5,26]. In another study no differences were observed in terms of overall incidence of second tumors between 2D-conventional and 3D-CRT but only an advantage in patients undergoing 3D-CRT in terms of second rectal tumors.…”
Section: Discussionmentioning
confidence: 96%
“…In the past, even if the results are somehow contradictory [26] and the incidence of second tumors could also be attributed to age and lifestyles [6], several analyses showed an increased risk for second tumors after EBRT of PCa [3][4][5]24]. Probably these data should be considered with caution.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been many studies of secondary cancer risk after EBRT, fewer have analyzed secondary cancer risk after brachytherapy (15‐19) . For example, although cervical cancer is usually treated with high‐dose‐rate (HDR) brachytherapy, few studies have analyzed secondary cancer risk due to HDR brachytherapy in patients with cervical cancer.…”
Section: Introductionmentioning
confidence: 99%